Experimental and numerical investigation of near-field rotor aeroacoustics - Stepanov, R.; Pakhov, V.; Bozhenko, A.; Batrakov, A.; Kusyumov, A.; Mikhailov, S.; Barakos, G.N. (My University, 2018)
This work presents comparisons between experimental and numerical estimates of near-field rotor aeroacoustics in hover. The experiments took place at the Kazan National Research Technical University named after A. N. Tupolev (Kazan Aviation Institute). A set of rotor blades with NACA-0012 aerofoil sections was used to obtain the sound pressure distribution using a linear array of microphones. It is shown that CFD and experimental results are in good agreement suggesting that the obtained test data can be useful as a validation case for development of CFD tools.